2022
DOI: 10.1001/jamanetworkopen.2022.9712
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Characteristics Associated With the Failure of Nonoperative Management of Uncomplicated Appendicitis in Children

Abstract: Key Points Question What factors are associated with the failure of nonoperative management of appendicitis, and do patient-reported outcomes differ between those whose treatment succeeded vs those whose treatment failed? Findings In this planned subgroup analysis of a nonrandomized clinical trial of 1068 patients, higher pain scores at presentation were associated with increased risk of in-hospital treatment failure, and longer pain duration was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
7
0
3
Order By: Relevance
“…Normally, there are two reasons for such wide range as follows: (1)Preoperative imaging such as Computed Tomography(CT) and Ultrasound (US), has widespread used to greatly reduce the proportion of negative appendices in recent years. CT has been shown greater sensitivity and specificity than US for the diagnosis of appendicitis [ 63 65 ]; (2)Some considered completely normal appendicitis as a negative appendectomy, while the others included hyperplasia, atrophy and fibrosis. The present study applies the latter definition.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, there are two reasons for such wide range as follows: (1)Preoperative imaging such as Computed Tomography(CT) and Ultrasound (US), has widespread used to greatly reduce the proportion of negative appendices in recent years. CT has been shown greater sensitivity and specificity than US for the diagnosis of appendicitis [ 63 65 ]; (2)Some considered completely normal appendicitis as a negative appendectomy, while the others included hyperplasia, atrophy and fibrosis. The present study applies the latter definition.…”
Section: Discussionmentioning
confidence: 99%
“…Minneci PC reported that patients who selected nonoperative management had high quality-of-life scores and remained satis ed with their health care decision at both 30 days and 1 year [70].…”
Section: Discussionmentioning
confidence: 99%
“…Entre as crianças submetidas ao tratamento não operatório de apendicite não complicada, vários fatores foram associados ao sucesso do tratamento, incluindo escores iniciais de dor, duração da dor e satisfação com os cuidados de saúde. A identificação desses fatores pode ajudar a melhorar a seleção de pacientes e otimizar os resultados do tratamento (MINNECI PC,et al 2022).…”
Section: Métodosunclassified
“…Estudos clínicos randomizados têm demonstrado consistentemente que a terapia antibiótica pode ser eficaz no tratamento da apendicite aguda não complicada, com taxas de sucesso que variam entre 67% e 73,8% em um ano, resultando em menos dias de incapacidade em comparação com a apendicectomia (HAIJANEN J, et al 2021). A abordagem não operatória pode oferecer uma alternativa segura e eficaz para muitos pacientes, especialmente em comparação com a cirurgia, que pode estar associada a complicações em até 15% dos casos, com 1% a 7% desses casos resultando em complicações graves (MINNECI PC,et al 2022).…”
Section: Introductionunclassified
See 1 more Smart Citation